1999
DOI: 10.1523/jneurosci.19-09-03440.1999
|View full text |Cite
|
Sign up to set email alerts
|

FcεRII/CD23 Is Expressed in Parkinson’s Disease and Induces,In Vitro,Production of Nitric Oxide and Tumor Necrosis Factor-α in Glial Cells

Abstract: Oxidative stress is thought to be involved in the mechanism of nerve cell death in Parkinson's disease (PD). Among several toxic oxidative species, nitric oxide (NO) has been proposed as a key element on the basis of the increased density of glial cells expressing inducible nitric oxide synthase (iNOS) in the substantia nigra (SN) of patients with PD. However, the mechanism of iNOS induction in the CNS is poorly understood, especially under pathological conditions. Because cytokines and FcepsilonRII/CD23 antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
245
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 379 publications
(254 citation statements)
references
References 44 publications
8
245
0
1
Order By: Relevance
“…SOD-catalase (100 and 150 U/ml, respectively) were added at the same time with rotenone and LPS. Seven days later, neurotoxicity was determined by PD have derived from postmortem analyses of PD brains in which microglial activation, elevated levels of proinflammatory mediators such as TNF␣, IL-1␤, and NO, and evidence of ROS production have been detected in the substantia nigra (McGeer et al, 1988;Cassarino et al, 1997;Hunot et al, 1999;Nagatsu et al, 2000). However, it is not clear whether these inflammatory "footprints" observed in the late stages of the pathogenesis of PD may merely be a reflection of reactive gliosis after the occurrence of the initial neuronal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…SOD-catalase (100 and 150 U/ml, respectively) were added at the same time with rotenone and LPS. Seven days later, neurotoxicity was determined by PD have derived from postmortem analyses of PD brains in which microglial activation, elevated levels of proinflammatory mediators such as TNF␣, IL-1␤, and NO, and evidence of ROS production have been detected in the substantia nigra (McGeer et al, 1988;Cassarino et al, 1997;Hunot et al, 1999;Nagatsu et al, 2000). However, it is not clear whether these inflammatory "footprints" observed in the late stages of the pathogenesis of PD may merely be a reflection of reactive gliosis after the occurrence of the initial neuronal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oxidative stress also other mechanisms have been proposed to be involved in selective DA neuron degeneration in PD, including excitotoxicity, intracellular calcium and metal ion rise, neurofibrillary tangle formation and disruption of the cytoskeletal transport [112]. More recently, neuroinflammation and microglial activation have been implicated in the neurodegenerative process in PD, as initially suggested by McGeer et al [155] and then by several authors ( [77,89,95,97,104,102,107,148,168]). In fact, studies accumulated over the last two decades have clearly indicated the presence of an abnormal glial response in postmortem nervous system of PD patients.…”
Section: Parkinson's Disease and Neuroinflammationmentioning
confidence: 95%
“…No staining was observed under these conditions. Fluorescent double-staining experiments were performed on mesencephalic sections mounted on gelatin-double-coated slides, as described previously (23), to analyze simultaneously caspase-3 and TH.…”
Section: Methodsmentioning
confidence: 99%